Swedish Whiteness, German Multiculturalism, French National Identity, and American Racial Profiling: Transnational Perspectives on Jonas Hassen Khemiri’s Invasion! - Gindt, Dirk (Nordic Theatre Studies, 2022)
Populated by characters from the Middle East, North Africa, Southeast Asia, and Sweden, Jonas Hassen Khemiri’s debut play, Invasion! (2006), marked one of the first intercultural theatrical events on a mainstream Swedish stage. It unapologetically confronted audiences with the consequences of stereotypical representations of Muslim men as fundamentalist terrorists and further criticized the notion of “Swedishness” for not just working as a mere designation of nationality and citizenship, but also a silent, yet powerful signifier of whiteness. Moreover, Invasion! was the first play to be performed in a mainstream theatre by a cast that had an intercultural and international background and could effortlessly switch between standard Swedish (rikssvenska) and suburban Swedish (ortenspråk). Acknowledging the fifteenth anniversary of Invasion!, this article looks back upon the watershed of director Farnaz Arbabi’s original production and the play’s subsequent transnational impact. How did a play that was defiantly at odds with the hegemonic whiteness of the performing arts in Sweden, at that point in time, not only become a modern classic that found its way into the university curricula, but went on to garner an impressively transnational success? What exactly captured the interest and attention of theatre artists in Germany, France, the US, and many other countries? And how did international reviewers react to and interpret the work? What interests me specifically is to study how the play has ‘travelled’, how its characters and themes have migrated to different national and linguistic contexts, engendered new creative networks and transnational dialogues as well as unfolded multiple layers of cultural translations in the process. A genuine understanding and appreciation of Khemiri’s work, I suggest, necessitates a transnational outlook that, in turn, sheds light on Nordic theatre and performance as increasingly intercultural and motivated by concerns that are not regional but global.